From exploratory research to structural models: A multilevel lexical approach to studying the image of marketing objects - Kolańska-Stronka, Magdalena; Gorbaniuk, Oleg; Wilczewski, Michał (Przegląd Wschodnioeuropejski, 2020)
The key problem in studies of marketing objects (e.g., brands, political parties) is the lack of agreement on the universal dimensions through which such objects are perceived, as well as on methodologies allowing their identification. As a result, researchers often use structural models (and instruments) that lack ecological validity. We offer a solution to that problem by presenting a methodology that draws on lexical research and which has allowed researchers to establish universal dimensions of personality perception in psychology. By discussing the theoretical and methodological tenets of the multilevel lexical approach to exploring images of marketing objects, we also overcome another problem of neglecting the hierarchical structure of the phenomena and data.